Digitalization for Traditional Cakes from Small and Medium Enterprises by Malay Jambi Women - Refnida Refnida; Siti Syuhada; Fachruddiansyah Muslim; Mayasari Mayasari (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines the role of digitalization in enhancing the competitiveness of traditional cakes produced by small and medium enterprises (SMEs) owned and managed by Malay Jambi women, as part of the creative economy. The objective is to examine how social media platforms and user-friendly design tools contribute to enhancing product innovation, marketing, and business sustainability. Employing a Design-Based Research (DBR) approach with mixed methods, the study involved 30 female entrepreneurs engaged in traditional cake businesses in Jambi. Data were collected through observations, interviews, and surveys, followed by quantitative analysis using t-tests. The results indicate that digitalization, particularly the use of Instagram for promotion and Canva for packaging design, significantly improves product visibility, consumer appeal, and market access. Innovations in packaging and presentation strengthen customer engagement and increase sales. The findings conclude that digital-based product development empowers women entrepreneurs to overcome market limitations and contributes to local economic resilience. This research contributes by providing a new empirical model for integrating cultural heritage with digital transformation. Theoretically, the study expands our understanding of how digitalization can function not only as a business strategy but also as a catalyst for women's empowerment and the development of a sustainable creative economy within local socio-cultural contexts.